Adaptive Leadership and Performance of Deposit Taking Microfinance Institutions in Nairobi County, Kenya - Joseph Opanda Namutala (PAC University, 2024)
The study investigated the effect of adaptive leadership on performance of Deposit Taking Microfinance Institutions (DTMFIs) in Nairobi County. In particular, the study set out to; determine the effect of situational challenges, adaptive leadership behavior, adaptive work, and emotional intelligence on the performance of Deposit Taking Microfinance Institutions in Nairobi County. The main theory that anchored the study was Adaptive leadership theory which was supported by organizational learning theory, balanced score card (BSC) model, and emotional intelligence theory. The study adopted the postpositivist philosophy. The research design was descriptive and explanatory with a target population of 298 senior, middle-level, and lower-level managers drawn from 12 Deposit Taking Microfinance Institutions in Nairobi County. Primary data was collected using a semistructured questionnaire from 102 out of 169 respondents selected from the target population. Descriptive analysis was done using mean, frequency and standard deviation while inferential analysis was done using correlation and regression analysis. The findings indicated that adaptive leadership had a positive and significant effect on the performance of DTMFIs. Further, it was established that situational challenges, adaptive leadership behavior, adaptive work, and emotional intelligence had positive and significant effect on the performance of DTMFIs in Nairobi County. The study concluded that adaptive leadership had a positive and statistically significant effect on the performance of DTMFIs in Nairobi County. The study therefore recommends that senior, middle-level, and lowerlevel managers should focus on various elements of adaptive leadership for improved performance of DTMFIs in Nairobi County. Further investigation can be done on adaptive work and emotional intelligence in different contexts to find out the consistency of its effect on performance